2019
DOI: 10.1016/j.talanta.2019.120148
|View full text |Cite
|
Sign up to set email alerts
|

Residual biomass of coffee as a binding agent in diffusive gradients in thin-films technique for Cd, Cu, Ni, Pb and Zn measurement in waters

Abstract: Spent coffee grounds (SCG) immobilized in agarose gel are proposed as a novel binding agent for application in the Diffusive Gradients in Thin films (DGT) technique for the determination of Cd, Cu, Ni, Pb and Zn in waters. The SCG-agarose gel was characterized by Scanning Electron Microscopy, Energy Dispersive X-ray Spectrometry and Porosimetry by nitrogen adsorption. Elution of analytes from the binding agent was effectively performed with 2 mol L −1 HCl. The effects of key DGT parameters (e.g. immersion time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…We chose 3 M HNO 3 as the best eluent for use in the present study. The elution efficiency of Cd was 98 ± 0.9%, which was higher than that of novel spent coffee grounds gel (eluting efficiency 62.9 ± 3.7%; Yabuki et al 2019) and traditional Chelex-100 gel (eluting efficiency 83.9 ± 2.7%; Zhang and Davison 1995). Not only that, SA-PGA gel with higher eluting efficiency was more helpful for the capture and determination of target substance more accurately.…”
Section: Adsorption Performancementioning
confidence: 82%
See 3 more Smart Citations
“…We chose 3 M HNO 3 as the best eluent for use in the present study. The elution efficiency of Cd was 98 ± 0.9%, which was higher than that of novel spent coffee grounds gel (eluting efficiency 62.9 ± 3.7%; Yabuki et al 2019) and traditional Chelex-100 gel (eluting efficiency 83.9 ± 2.7%; Zhang and Davison 1995). Not only that, SA-PGA gel with higher eluting efficiency was more helpful for the capture and determination of target substance more accurately.…”
Section: Adsorption Performancementioning
confidence: 82%
“…The pH ranged from 5 to 9, the Cd adsorption efficiency of the DGT did not change significantly, and the value of C DGT /C soln tended to 1 (Supplemental Data, Figure S2A). Regarding DGT for the same metal target, conclusions can be drawn; SA‐PGA‐DGT is applied to a wider pH range than Saccharomyces cerevisiae DGT (pH 4.5–7.5), spent coffee grounds DGT (pH 3.5–8.0), and poly(ethyleneimine) and 2‐pyridinecarboxaldehyde DGT (pH 4–8.5; Menegario et al 2010; Fan et al 2013; Yabuki et al 2019). Compared with the reported pH range of Chelex‐100 resin (Zhang and Davison 1995), the quantitative binding of SA‐PGA‐DGT at pH 5 to 9 was equally reliable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] Various adsorbents, including biomass, polymers, activated carbons and minerals, have been applied to remove Pb(II) from contaminated wastewater. [14][15][16][17] Moreover, it has been observed that these adsorbents require further modications to increase the number of active binding sites and make them readily available for adsorption. 18,19 Although some of the abovementioned adsorbents are able to remove Pb(II) from contaminated wastewater, high cost is still the main concern or disadvantage of these adsorbents in practical applications.…”
Section: Introductionmentioning
confidence: 99%